The digestive tract as an essential organ for water acquisition in marine teleosts: lessons from euryhaline eels - Takei, Yoshio (Zoological letters, 2021)
Adaptation to a hypertonic marine environment is one of the major topics in animal physiology research. Marine teleosts lose water osmotically from the gills and compensate for this loss by drinking surrounding seawater and absorbing water from the intestine. This situation is in contrast to that in mammals, which experience a net osmotic loss of water after drinking seawater. Water absorption in fishes is made possible by (1) removal of monovalent ions (desalinization) by the esophagus, (2) removal of divalent ions as carbonate (Mg/CaCO 3 ) precipitates promoted by HCO 3 − secretion, and (3) facilitation of NaCl and water absorption from diluted seawater by the intestine using a suite of unique transporters. As a result, 70–85% of ingested seawater is absorbed during its passage through the digestive tract. Thus, the digestive tract is an essential organ for marine teleost survival in the hypertonic seawater environment. The eel is a species that has been frequently used for osmoregulation research in laboratories worldwide. The eel possesses many advantages as an experimental animal for osmoregulation studies, one of which is its outstanding euryhalinity, which enables researchers to examine changes in the structure and function of the digestive tract after direct transfer from freshwater to seawater. In recent years, the molecular mechanisms of ion and water transport across epithelial cells (the transcellular route) and through tight junctions (the paracellular route) have been elucidated for the esophagus and intestine. Thanks to the rapid progress in analytical methods for genome databases on teleosts, including the eel, the molecular identities of transporters, channels, pumps and junctional proteins have been clarified at the isoform level. As 10 y have passed since the previous reviews on this subject, it seems relevant and timely to summarize recent progress in research on the molecular mechanisms of water and ion transport in the digestive tract in eels and to compare the mechanisms with those of other teleosts and mammals from comparative and evolutionary viewpoints. We also propose future directions for this research field to achieve integrative understanding of the role of the digestive tract in adaptation to seawater with regard to pathways/mechanisms including the paracellular route, divalent ion absorption, metabolon formation and cellular trafficking of transporters. Notably, some of these have already attracted practical attention in laboratories.